1997
DOI: 10.3354/meps160217
|View full text |Cite
|
Sign up to set email alerts
|

A model of larval dispersion coupling wind-driven currents and vertical larval behaviour:application to the recruitment of the annelid Owenia fusiformis in Banyuls Bay, France

Abstract: ABSTRACT. We present a mathematical model of larval dispersal into a coastal zone dominated by wlnd-driven currents: larvae are considered as active particles tracked by the 3-D (3-dimensional) velocities calculated by a physical model sophisticated enough to give a good representation of the 3-D structure of wind-driven currents. As a n application, we model the larval recruitment of the annelid Owenia fusiformis in Banyuls Bay, France, located at the southwest extremity of the Gulf of Lions. The currents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…If the potential for limited larval dispersal and high mortality rates inferred from our data are a general feature of similar coastal regions, then populations of sedentary benthic invertebrates with planktonic larvae may be disconnected at small spatial scales, as suggested by recent observational (McQuaid & Phillips 2000, Porri et al 2006) and modeling studies (Verdier-Bonnet et al 1997). Future efforts to model the relationship between coastal oceanography and benthic population dynamics must shift from an emphasis on mesoscale processes to a better description of inner-shelf variability and its effect on dispersal and self-recruitment.…”
Section: Mortality Estimatesmentioning
confidence: 94%
“…If the potential for limited larval dispersal and high mortality rates inferred from our data are a general feature of similar coastal regions, then populations of sedentary benthic invertebrates with planktonic larvae may be disconnected at small spatial scales, as suggested by recent observational (McQuaid & Phillips 2000, Porri et al 2006) and modeling studies (Verdier-Bonnet et al 1997). Future efforts to model the relationship between coastal oceanography and benthic population dynamics must shift from an emphasis on mesoscale processes to a better description of inner-shelf variability and its effect on dispersal and self-recruitment.…”
Section: Mortality Estimatesmentioning
confidence: 94%
“…The mathematical model of Verdier-Bonnet et al (1997) predicts that, under the most common wind conditions near Banyuls in France, populations of polychaets with larvae in the water for 4 wk would show little exchange between bays < 2 km apart. Todd et al (1998), working with allozymes, found that populations of a nudibranch with pelagic lecithotrophic larvae were closed on surprisingly small spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…These currents are usually driven by wind, which is one of the three principal agents controlling the movement of larval fish and invertebrates on the continental shelf (Epifanio and Garvine 2001). Evidence indicates that these currents might affect the recruitment of invertebrates such as crabs (Blanton et al 1995;Wing et al 1995;Shanks 1998), clams (Weissberger and Grassle 2003;Ma 2005;Shanks and Brink 2005), sea urchins (Wing et al 1995), annelids (Verdier-Bonnet et al 1997), and others, although the association with the vertical current might be weak (e.g., Shanks 1998). However, only a few studies have explained the differences found in the recruitment intensity of fish as due to upwelling or downwelling flow (Reiss and McConaugha 1999;Miller and Shanks 2005), and none of these have referred to coral-reef fishes.…”
mentioning
confidence: 99%